Degradation of the remanent ferromagnetic state under the action of ferroelectric relaxation processes in Co/(1-x)PMN-xPT/Co hybrids: Possible implications on cryogenic and room-temperature applications - Stamopoulos, D.; Zeibekis, M.; Vertsioti, G.; Zhang, S.J. (JOURNAL OF APPLIED PHYSICS, 2014)
Low-dimensional hybrid structures of heterogeneous constituents usually exhibit abnormal properties, a fact that makes such hybrids attractive for various cryogenic and room-temperature applications. Here, we studied Co/(1 - x)Pb(Mg1/3Nb2/3)O-3-xPbTiO(3)/Co (Co/PMN-xPT/Co) with x = 0.29 and 0.30, specifically focusing on the evolution of the remanent ferromagnetic state, m(rem) of the Co outer layers in the whole temperature range from 300K down to 10 K, upon application of an external electric field, E-ex. We observed that m(rem) was vulnerable to degradation through the occurrence of electric field-induced magnetic instabilities (EMIs) that appeared only when E-ex not equal 0 kV/cm and were facilitated as E-ex increases. However, EMIs completely ceased below a characteristic temperature T-ces = 170 K even for the maximum vertical bar E-ex vertical bar = 5 kV/cm applied in this work. A direct comparison of the magnetization data of the Co/PMN-xPT/Co hybrids reported here with the electromechanical properties of the parent PMN-xPT crystals plausibly indicates that EMIs are motivated by the coupling of the ferromagnetic domains of the Co outer layers with the ferroelectric domains of the PMN-xPT crystal. These results highlight the drawback of EMIs in relevant hybrids and delimit the temperature regime for the reliable operation of the Co/PMN-xPT/Co ones studied here. (c) 2014 AIP Publishing LLC.